North American Tunneling : 2010 Proceedings - Eckert, Lawrence R. (Society for Mining, Metallurgy, and Exploration, Inc., 2010)
North American Tunneling 2010 underscores the important role that the tunneling industry plays worldwide in the development of underground space, transportation systems, conveyance systems, and other forms of sustainable infrastructure. The proceedings describe the evolving nature of underground work, methods, and technology. This book documents the challenges faced and the lessons learned while advancing projects in support of a sustainable future.